Challenges and potentialities of implementing an experience of a mental health matrix support in primary health care - Tavares, André Luís Bezerra (2023)
Introduction: Mental health care in Brazil underwent advances with the Psychiatric Reform, introducing new practices and improving strategies in the Psychosocial Care Network such as Primary Health Care. In this new reality, matrix support stands out as a new way of producing shared care between specialized teams and the Family Health Strategy (FHS) team. However, there are still difficulties in implementing its actions. Objective: To describe the challenges and potentialities in the implementation of a proposed methodology for matrix support in Mental Health in Primary Health Care. Methods: This is a qualitative study, whose population consisted of five physicians participating in an intervention to implement a matrix support in two Family Health Centers, three of which were FHS physicians and two who worked as matrix supporters. For data collection, the following were included: systematic observation, unstructured interview, group interviews and documentary research. A pretest was carried out with a FHS physician and, after this phase, five individual and three group interviews were carried out, one group with physicians from the FHS, another with the matrix supporters and one with the five physicians. For data analysis, the Minayo’s thematic analysis was used. Results: Based on the thematic analysis, four categories of analysis emerged from the interviewees’ statements: “definition of matrix support,” “how to implement and develop matrix support,” “advantages and potentialities of matrix support,” and “difficulties for the process.” Conclusions: Matrix support in mental health is an extremely useful tool and must be widely expanded in the current health scenario. In this study, the perception of the advantages and the motivation to carry out the actions by the interviewees demonstrate how this is a strategy that can be implemented and multiplied.